Choreographing from within : developing the habit of inquiry as an artist. - Green, Diana F., ....- (Champaign : Human Kinetics, 2010)
One school of thought regarding choreography says to teach only the rules of fundamental design and form and have students create from formulas. Another school of thought eschews the fundamentals and focuses on creativity. Author Diana Green espouses both theories and blends them beautifully in Choreographing From Within: Developing a Habit of Inquiry as an Artist. Her approach to integrating the art and craft of choreography grounds students in the fundamentals and takes the fear out of creativity. Green uses an inquiry-based approach to engage students, placing them at the center of the learning and allowing for multiple pathways of learning. Rather than present a cookbook approach with recipes to follow, Green offers a thorough understanding of the medium, provides examples, and allows students to learn, explore, and create based on their own unique styles. Choreographing From Within will help students * learn to create movement that originates from a specific intent, * understand
The elements of choreography, * synthesize those elements through a series of exercises in which they are given explicit instruction, and * break formulaic boundaries as they create their own dances. The text contains assignments that reinforce the concepts the students learn in each chapter (including the elements of energy, space, time, and quality; partnering; transitions; and formulas). Each choreographic concept is explored through warm-up exercises, moves on to improvisations, and then focuses on students' discovery through reflective questioning, discussions, and short movement studies. The text provides tools for students and their instructors to evaluate and document their progress through class critiques, journal writing, rubrics, digital portfolios, and critical thinking essays. Students can retest their discoveries by completing exercises that focus on breaking the rules they learned. In this way, each student is encouraged to develop a unique creative style to be used in
His or her own finished work, be it for solo, duet, or small-group choreography. Part I focuses on the process of choreography and how to be intentionally creative. Part II introduces students to the elements of movement, helping them to analyze the separate elements before they learn to synthesize them in part III, where music is added. Students also learn how to apply transitions in their work, use formulas to manipulate movement, and explore with props and various numbers of dancers. Finally, in part IV, students begin planning finished pieces of choreography using methods of refining and forming. The book's dynamic photos illustrate the concepts covered in the book, helping to shape students' awareness and inspire them in their own creations. Because the text is designed for use with all dance techniques, the glossary terms clarify communication across various dance styles. Choreographing From Within helps students find the unique artist within themselves. That unique artist springs from
The inquiry-based approach that puts students in the driver's seat and provides numerous pathways and tools for them to develop their abilities to their fullest.
Keywords: Choreografie